A spatial correlation model of peak ground acceleration and response spectra based on data of the Istanbul Earthquake Rapid Response and Early Warning System. Issue 85 (June 2016) - Wagener, Thomas; Goda, Katsuichiro; Erdik, Mustafa; Daniell, James; Wenzel, Friedemann
Abstract: Ground motion intensity measures such as the peak ground acceleration (PGA) and the pseudo-spectral acceleration (PSA) at two sites due to the same seismic event are correlated. The spatial correlation needs to be considered when modeling ground-motion fields for seismic loss assessments, since it can have a significant influence on the statistical moments and probability distribution of aggregated seismic loss of a building portfolio. Empirical models of spatial correlation of ground motion intensity measures exist only for a few seismic regions in the world such as Japan, Taiwan and California, since for this purpose a dense observation network of earthquake ground motion is required. The Istanbul Earthquake Rapid Response and Early Warning System (IERREWS) provides one such dense array with station spacing of typically 2 km in the urban area of Istanbul. Based on the records of eight small to moderate ( M w 3.5– M w 5.1) events, which occurred since 2003 in the Marmara region, we establish a model of intra-event spatial correlation for PGA and PSA up to the natural period of 1.0 s. The results indicate that the correlation coefficients of PGA and short-period PSA decay rapidly with increasing interstation distance, resulting in correlation lengths of approximately 3–4 km, while correlation lengths at longer natural periods (above 0.5 s) exceed 6 km. Finally, we implement the correlation model in a Monte Carlo simulation to evaluate economic loss in Istanbul's district Zeytinburnu due to a M w 7.2 scenario earthquake. Highlights: Empirical model of ground motion correlation for Istanbul. Small correlation lengths from a dense accelerometer array. Demonstration of relevance for loss assessment.